Evolution of a group - Haynes, Robert; Walter, Thomas (Pacific Grove, Canada : Brooks/Cole, 2000)
This video is a compilation of the significant group process and leadership techniques that occured over a three-day residential group therapy session. You will see the development of the group process and how the leaders facilitated that process as the group moved through the four stages : initial, transition, working and ending
Editor, Dan Tomer
Narrator: Annie Hansen
Keywords: Leadership -- Study and teaching